Rate and Determinants of Slow Flow / No-Reflow in Patients Undergoing Primary Percutaneous Coronary Intervention at Sandaman Provincial Hospital Quetta - Abdul Wadood Kakar, Anil Kumar, Javed Khurshed Shaikh, Muhammad Hashim Kalwar, Muhammad Hassan Butt, Nadeem Hassan Rizvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: We investigated the rate of slow/no flow during percutaneous coronary intervention, the clinical and angiographical predictor and the immediate hemodynamic role of slow / no flow. Material & Method: The cross-sectional study was done at Sandaman Provincial Hospital, the Loralai Medical Collage Loralai, Bolan University of Medical and Health Sciences Quetta for six months from 1st July, 2021 to 31st December, 2021. We included ST-elevation myocardial infarction patients who got primary percutaneous coronary intervention (PCI). Patient information, including demographic and clinical data was collected. In this study, thrombolysis in myocardial infarction was used to determine the antegrade flow. There was an evaluation of the existence, predictors, and consequences of slow/no flow in the patients. SPSS 21 was used for data analysis. Results: Among the 300 patients, 283 (80.9%) were males. There were 54 (18.0%) patients who had angiographic slow/no flow during the procedure. TIMI grades were 0 in 13 (4.33%), 1 in 16 (5.33%), and 2 in 25 (8.33%) patients in these affected groups in the study. Smoking status was significantly different between slow and no flow (p=0.023). We found significant associations between prior MI, nonappearance of pre-infarction anginal symptoms, and any cerebrovascular disease with slow/no blood flow (p<0.05). The class III or IV Killip score was significantly higher in the slow/low flow group than the normal-flow group (p<0.05). Intracoronary adenosine and epinephrine were the most often used medications for pharmacological therapy of no/slow flow. The hemodynamic instability of two of the patients (3.70%) of the ventricular tachycardia treatment (VT) cases led to their deaths, while the stability of two (3.70%) of the patients’ VTs required pharmaceutical cardioversion. Conclusion: The occurrence of slow/no flow can be predicted with a history and angiographical feature.